2020
DOI: 10.1093/sysbio/syaa093
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Phylogenetic Signal and Adaptation in Papionin Cranial Shape by Decomposing Variation at Different Spatial Scales

Abstract: This document corresponds to the worked example of the paper Detecting phylogenetic signal and adaptation in papionin cranial shape by decomposing variation at different spatial scales (Grunstra et al.). The dataset is a set of 70 2D landmarks on the midsagittal plane of the skull in 67 primates from 18 species (16 papionin taxa, 2 outgroups). The example below describes how to decompose shape variation into total, outline, and residual shape (approach 1) or into large-scale and small-scale shape (approach 2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…These small‐scale features may thus be more strongly subject to evolutionary drift across species and reduced stabilizing selection within species as compared with large‐scale features. Accordingly, Grunstra et al (2021) found that small‐scale cranial shape features better reflect papionin phylogenetic history than large‐scale features, whereas individuals better clustered into species for the large‐scale shape features.…”
Section: Morphological Integration Modularity and Spatial Scalementioning
confidence: 99%
“…These small‐scale features may thus be more strongly subject to evolutionary drift across species and reduced stabilizing selection within species as compared with large‐scale features. Accordingly, Grunstra et al (2021) found that small‐scale cranial shape features better reflect papionin phylogenetic history than large‐scale features, whereas individuals better clustered into species for the large‐scale shape features.…”
Section: Morphological Integration Modularity and Spatial Scalementioning
confidence: 99%
“…It should be noted that the observed values are closer to zero, corresponding to the theoretical total disintegration of individual landmarks, than those previously found for any multicellular organisms or tissues [28,[36][37][38]. Thus, it appears that morphogenesis at the single-cell level can indeed lead to structures whose integration is markedly different from that of multicellular organisms.…”
Section: Discussionmentioning
confidence: 53%
“…Phylogenetic signals have been used to answer a variety of evolutionary and ecology related questions related to adaptation (Bozinovic et al, 2007;Grunstra et al, 2021), evolutionary niches (Hof et al, 2010;Silvertown et al, 2005), and hybridization (Mitchell et al, 2019;Whitney et al, 2010). The power of Pagel's λ in phylogenetic signal analysis, however, does increase with the size of the phylogeny (Münkemüller et al, 2012), which is why it is important to collect as much trait data as possible across as many taxa as possible.…”
Section: Measuring Phylogenetic Relationshipsmentioning
confidence: 99%